ANALISIS PERSEPSI GENDER PADA ANAK MELALUI PRAKTIK SENI GRAFIS BERSAMA KOMUNITAS YUK BELAJAR SENI (YBS) - Rohmah, Nurtaria; Adrianto, Aditya Eko (TEXTURE Art and Culture Journal, 2024)
This study aims to explore gender perceptions in children's graphic art practices based on observations of their family environment through the YBS community at SD Negeri 02 Gentungan using a contextual approach. Data were collected through graphic artworks and interviews, employing high print techniques with eva foam matrices, where children selected 8professionsassociatedwithmasculinityandfemininity.Thefindingsrevealthat10-year-old children have recognized their gender roles, reflected in their choice of professions aligned withtheirgender.However,thereareindicationsofpotentialsubversionofgendernorms,as someboys choseprofessions,like acookand a tailor. These findingssupport Judith Butler's view that gender identity and roles are formed through the repetition of observed actions, demonstrating how familial and social contexts shape children's gender identity and career choices in line with the concept of gender performativity